Communication between family carers and health professionals about end-of-life care for older people in the acute hospital setting: a qualitative study - Caswell, Glenys; Pollock, Kristian; Harwood, Rowan; Porock, Davina (BioMed Central, 2015)
Background: This paper focuses on communication between hospital staff and family carers of patients dying on acute hospital wards, with an emphasis on the family carers’ perspective. The age at which people in the UK die is increasing and many continue to die in the acute hospital setting. Concerns have been expressed about poor quality end of life care in hospitals, in particular regarding communication between staff and relatives. This research aimed to understand the factors and processes which affect the quality of care provided to frail older people who are dying in hospital and their family carers. Methods: The study used mixed qualitative methods, involving non-participant observation, semi-structured interviews and a review of case notes. Four acute wards in an English University teaching hospital formed the setting: an admissions unit, two health care of older people wards and a specialist medical and mental health unit for older people. Thirty-two members of staff took part in interviews, five members of the palliative care team participated in a focus group and 13 bereaved family carers were interviewed. In all, 245 hours of observation were carried out including all days of the week and all hours of the day. Forty-two individual patient cases were constructed where the patient had died on the wards during the course of the study. Thirty three cases included direct observations of patient care. Interviews were completed with 12 bereaved family carers of ten patient cases. Results: Carers’ experience of the end of life care of their relative was enhanced when mutual understanding was achieved with healthcare professionals. However, some carers reported communication to be ineffective. They felt unsure about what was happening with their relative and were distressed by the experience of their relative’s end of life care. Conclusions: Establishing a concordant relationship, based on negotiated understanding of shared perspectives, can help to improve communication between healthcare professionals and family carers of their patients.